THE APPLICATION OF PROBLEM SOLVING APPROACH IN IMPROVING JUNIOR HIGH SCHOOL STUDENTS’ MATHEMATICAL COMMUNICATION AND DISPOSITION SKILL - Imas Mulyasari; Euis Eti Rohaeti; Asep Ikin Sugandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This article is derived from the research result entitled “The Application of Problem Solving Approach in Improving Junior High School Students’ Mathematical Communication and Disposition Skill”. The research is purposed to see and analyze if there are some improvements in mathematical communication and disposition skill achievement of the students who have been treated using problem solving approach compared to the students who are still treated using conventional approach. The population of the research is all students at a junior high school in Subang regency. Out of these students,  40 students of class VIII D were chosen randomly as the experiment class, and 41 students of class VIII C have also been randomly chosen as the control class. The data in this research have then been analyzed using parametric and non-parametric statistic. The result of this analysis has shown that the achievement of experiment class students’ mathematical communication and disposition skill is better than the achievement of the control class students. The experiment class students’ mathematical disposition is also better than those of the control class. Lastly, the result also shows that there is some kind of correlation between the mathematical communication and mathematical disposition on the level of medium.